KAJIAN STILISTIKA TEKS BAHASA PEDALANGAN WAYANG PURWA GAYA SURAKARTA - D. Edi Subroto (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The purpose of this study is to identify and describe the linguistic elements used by the writers to obtain specific effects (expressivity function) in their creativity process. The study applied a model of descriptive qualitave research. The result of the study showed that in the use of comprehensive and significant linguistic elements, there was janturan (pathet 6, pathet 9, pathet manyura) especially anturan pathet 6. It was comprehensive because all linguistic elements are used altogether and they have supported the expressivity function. In using janturan pathet 6, the writers illustrate kebinatharaan (that of honorable god of Bathara) and the glory of a king, the prosperity and the conquest of a kingdom..